Modélisation numérique du flambement élastoplastique d’une poutre sous compression axiale - Grognec, Philippe Le; van, Anh Le (European Journal of Computational Mechanics, 2003)
In this paper, the problem of buckling and post-buckling of elastoplastic beams under axial compression in finite displacements and finite strains is resolved by the finite element method with a total Lagrangian formulation. The yield criterion is of the von Mises type with linear isotropic hardening in the framework of the Generalized Standard Materials theory. Numerical computations show the ability of the present formulation to describe any buckling mode in a systematic way and to reproduce numerically the main features of the theoretical plastic buckling problem.